2022
DOI: 10.3390/ijerph19020624
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Obesity in People with Normal Body Weight (MONW)—Review of Diagnostic Criteria

Abstract: Disorders of metabolic obesity with normal body weight (MONW) are widely recognized risk factors for the development of cardiovascular diseases and type 2 diabetes. Despite this, MONW is not diagnosed in clinical practice. There is no consensus on the definition of MONW, and measuring the degree of insulin resistance or obesity among apparently healthy, non-obese patients is not widely applicable. The awareness of the relationship between metabolic disorders such as MONW and a higher risk of mortality from car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 126 publications
0
35
0
3
Order By: Relevance
“…The prevalence of MONW features among the population is increasingly common and could be a health concern in the near future [ 34 , 35 ]. One of the main causes involved in the appearance of this phenotype is the intake of unbalanced diets [ 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of MONW features among the population is increasingly common and could be a health concern in the near future [ 34 , 35 ]. One of the main causes involved in the appearance of this phenotype is the intake of unbalanced diets [ 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Risk-scoring algorithms for undiagnosed diabetes are also available 43 , but there is no such approach for the main risk factors of type 2 diabetes, i.e., overweight, obesity, and MetS. The purpose of screening such conditions resides in well-established data about their preventability with adopting healthy lifestyle behaviours 44 and because people of normal weight are not always metabolically healthy 45 and at the opposite, the obesity phenotype can associate with no or little evidence of metabolic dysfunction 46 . We have exploited the potential of non-invasive, quantitative, and objective ERG by introducing a new and simple modality to record spontaneous activity of the retina and combined it with a supervised machine learning-based model to predict early risk factors of DR. Our data support the robustness of the random forest system in the screening of early risk factors for DR and imply its translation into clinical use thanks to automated platforms like the one we created (http://deepretinopathydx.inb.unam.mx/).…”
Section: Discussionmentioning
confidence: 99%
“…At the end, light stimulation (0.7 ms flashes of 0.38 log cd.s/m 2 ; MGS-2 white Mini-Ganzfeld Stimulator, LKC Technologies) was given to confirm retina function. If no classical evoked response was seen 93 , data were discarded.Human data descriptionA total of 520 adult subjects aged between 30 and 80 years (mean:45.27 ± 0.82 years, 265 females), metabolically healthy or with overweight, obesity, MetS, or diabetes but no DR, were enrolled between February 26, 2015 and December 2019 and from September 2021 and June 17, 2022, in the Mexican Institute of Ophthalmology (IMO) of Querétaro (mean age: 51.39 ± 1.49 years, 27 females), between November 11 and December 20, 2019 and from January 6 and May 26, 2022, in the Instituto de la Retina del Bajío (INDEREB) in Querétaro (mean age: 32.98 ± 2.07 years, 24 females), between August 10, 2021 and March 20, 2022 in the Asociación Para Evitar la Ceguera (APEC) in Mexico city (mean age: 45.77 ± 1.20 years, 119 females), and between August 10, 2021 and May 31, 2022 in the Clínica de Salud Visual (CSV) at ENES León UNAM in León (mean age: 44.96 ± 0.84 years, 96 females). 375 (age mean: 46.01 ± 0.98 years, 180 females) completed all tests required for the current study.…”
mentioning
confidence: 99%
“…A recent review reported the importance of early detection of metabolic obesity in patients with normal weight, in order to avoid undesirable consequences such as atherosclerosis, coronary artery disease or diabetes. Therefore, investigating this phenotype may represent another focus of our future research [46]. Moreover, no comparisons based on gender or age groups were performed and adjusting for confounders was difficult since the study cohort was relatively small.…”
Section: Discussionmentioning
confidence: 99%